2017
DOI: 10.1186/s12907-017-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of small, dense low density lipoprotein cholesterol—a possible antecedent of atherogenic lipoprotein phenotype in type 2 diabetes patients in Jos, North-Central Nigeria

Abstract: BackgroundThe global prevalence of type 2 diabetes is increasing. Dyslipidaemia is a known complication of diabetes mellitus manifesting frequently as cardiovascular diseases and stoke. Elevation of small, dense low density lipoprotein has been recognised as a component of the atherogenic lipoprotein phenotype associated with cardiovascular complications. We speculate that the elevation of this lipoprotein particle may be the antecedent of the atherogenic lipoprotein phenotype. This study therefore aims to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
(23 reference statements)
5
6
0
Order By: Relevance
“…Previous researches showed that diabetes patients had higher sdLDL-C levels [12,13], in our study, this result was con rmed. The LDL-C and sdLDL-C subfractions of 352 T2DM patients and 48 healthy people were analyzed, Pattern A had no obvious difference between T2DM patients and healthy people while Pattern B had higher expression in T2DM patients and had obvious differences (p < 0.001) (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous researches showed that diabetes patients had higher sdLDL-C levels [12,13], in our study, this result was con rmed. The LDL-C and sdLDL-C subfractions of 352 T2DM patients and 48 healthy people were analyzed, Pattern A had no obvious difference between T2DM patients and healthy people while Pattern B had higher expression in T2DM patients and had obvious differences (p < 0.001) (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Previous researches found that sdLDL-C levels were signi cantly higher in diabetes patients than in nondiabetic individuals [12,13]. To determine the expression of LDL-C and sdLDL-C in T2DM patients and healthy people, the Quantimetrix Lipoprint system was used for plasma sample analysis following the protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Previous researches showed that diabetes patients had higher sdLDL-C levels [12,13], in our study, this result was con rmed. The LDL-C and sdLDL-C subfractions of 352 T2DM patients and 48 healthy people were analyzed, Pattern A had no obvious difference between T2DM patients and healthy people while Pattern B had higher expression in T2DM patients and had obvious differences (p < 0.001) (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Previous researches found that sdLDL-C levels were signi cantly higher in diabetes patients than in nondiabetic individuals [13,14]. To determine the expression of LDL-C and sdLDL-C in T2DM patients and healthy people, the Quantimetrix Lipoprint system was used for plasma sample analysis following the protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation